Psychological Dynamics of Juvenile Inmates in LPKA: An Analysis Through Projective Assessment and TAT - Mu'mina Kahar; Dewi Ahmad (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2026)
This study aims to describe the psychological dynamics of juvenile inmates in LPKA an analysis through projective assessment and TAT. The research used a qualitative approach with a case study method involving one male adolescent identified as JP at the Special Child Development Institution (LPKA) Class II Ternate. Data collection techniques included observation, interviews, and psychological assessments consisting of Draw A Person (DAP), BAUM, House Tree Person (HTP), and Thematic Apperception Test (TAT). The results showed that the subject experienced complex psychological dynamics characterized by a high need for affiliation, emotional instability, low assertiveness, and maladaptive defense mechanisms. The subject tended to seek social acceptance and emotional closeness but experienced difficulties in self-control, decision making, and coping with social pressure. Emotional conditions that frequently emerged included anxiety, sadness, fear, guilt, and confusion. The subject also perceived the environment as a source of pressure, uncertainty, and conflict, especially related to family relationships and peer influence. Defense mechanisms such as avoidance, withdrawal, fantasy, and escape were commonly used by the subject in dealing with emotional stress. The findings indicate that psychological intervention focusing on emotional regulation, assertiveness skills, coping strategies, and social support is needed to support the psychological development of juvenile inmates.